Byōseki and pathography: Their commonalities and differences - Shinnosuke Saito (PCN Reports)
Abstract The German psychiatrist Paul Julius Möbius began to use the term Pathographie in a new sense: a psychiatric biography of a historical figure that focuses on their pathological aspects. Byōseki, which originated from Möbius's Pathographie, refers to a uniquely Japanese practice that explores the relationship between creativity and psychopathology. It is also the English translation of the term “pathography,” although the two terms differ significantly in both definition and usage. Originally, “pathography” was defined as “a description of disease,” but it eventually shifted to “a description of an individual or of a community through disease.” In the medical context, it is used mainly in the sense of “medical, psychiatric or psychoanalytic case study of a historical figure” or “patient narratives of illness.” In 1988, a newspaper article redefined pathography as a despicable and ugly biography that emphasizes not only disease but also the negative aspects of life. It can be noted that the above shifts in usage and the addition of new usages in the English term “pathography” were directly or indirectly influenced by Möbius's Pathographie. Although the essence of pathography is rooted in “patho‐ (disease, suffering),” the essence of Byōseki centers on “creativity.” The two overlap only when referring to medical, psychiatric or psychoanalytic case studies of historical figures. Under each of these terms, a rich body of descriptions of human experience has been archived. Knowing the exact definitions and usages of these terms is crucial for more people to properly access these archives.